The Ecological Adaptive Significance Of Littoraria scabra For Their Survivorship In Extreme Mangrove Environment Of Tombariri - Jans D Lalita; Jety K Rangan (Sam Ratulangi University, 2018)
This research was found the ecological adaptive significance for their survivorship in mangrove microhabitat was as follow resting place, avoiding high tide, finding food, lying larvae, avoid sunshine, and hiding from predators. Significance of clumped distribution was taken to reduce drying stress, temperature, fallen from substrate against wave strikes, feeding and reproduction activity, suitable habitat. Significance of population abundance to balance strong predation and response to pressure of nature selection for their survivorship. Key Words : Littoraria scabra, significance, ecology, survival, and mangrove ABSTRAKPenelitian ini menemukan bahwa signifikansi ekologi Littoraria scabra untuk survival di mikrohabitat mangrove Tombariri yang ekstrim adalah sebagai berikut berfungsi sebagai tempat istirahat, menghindari perendaman air, mencari makanan, meletakkan larva, menghindar cahaya dan bersembunyi dari predator-predator. Signifikansi L. scabra distribusi spasial mengelompok untuk mereduksi stres kekeringan, suhu, terlepas di substrat akibat gelombang, aktivitas makan, reproduksi, kecocokan habitat. Signifikansi distibusi mengelompok dengan populasi tinggi untuk mengimbangi kuatnya predasi serta merespons tekanan seleksi alam yang kuat demi kelangsungan hidupnya. Kata Kunci : Littoraria scabra, signifikansi, ekologi, survival dan mangrove